Evaluation of Indonesia-South Korea Cooperation in the Saemaul Undong Program in Sumbermulyo Village, Bantul, through a Participatory Approach - Agustiana, Radika Ayu; Anggraeni, Silvia Dian; Putri, Ardila; Hazmi, Adli (Journal of Paradiplomacy and City Networks, 2022)
In the 1970s, under President Park Chung Hee, the Saemaul Undong Movement was established to overcome the economic issues in underdeveloped and impoverished rural areas. Saemaul Undong is based on three principles: diligence, self-help, and cooperation. The program’s success in South Korea inspired the government to promote it to other countries, especially those in need. Sumbermulyo Village was one of three villages in the Yogyakarta Special Region (DIY) selected in 2015 when an MoU on collaboration with Saemaul Undong was signed between Indonesia and South Korea. The study revealed several differences in perceptions among the various stakeholders involved in the implementation of Saemaul Undong in Sumbermulyo Village, especially concerning funding, using several indicators of a participatory approach elaborated with in-depth interviews from relevant sources. The training program designed to alter people’s worldviews was sometimes criticized for taking too long to produce desirable results. The implementation deviated from the plan as a result.